Protest and pedagogy: The influence of civil unrest on teacher development and educational reforms in South Asia - Gyawali, Yadu Prasad; Mehndroo , Meghna (Journal of Interdisciplinary Studies in Education, 2024)
Drawing from the rich cultural heritage and diverse historical contexts of Nepal, India, Sri Lanka, and Myanmar, we examine how teachers adapt traditional and modern pedagogical methods in response to linguistic and cultural diversity. Colonial legacies in Sri Lanka and Myanmar, along with Nepal’s shifting sociopolitical climate, offer insights into the evolving identities of educators amidst systemic educational changes. The role of civil protests is analyzed as a catalyst for educational transformation, with particular emphasis on recent teacher demonstrations in Sri Lanka, underscoring the potential of disruptive movements to spur positive change. This analysis aligns Fullan’s principles with South Asia’s ongoing educational reforms, highlighting the resilience and adaptability of teachers in navigating cultural, historical, and political intersections.